2017
DOI: 10.1371/journal.pone.0170330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs in Response to Drought in Common Wild Rice (Oryza rufipogon Griff.) Shoots and Roots

Abstract: BackgroundDrought is the most important factor that limits rice production in drought-prone environments. Plant microRNAs (miRNAs) are involved in biotic and abiotic stress responses. Common wild rice (Oryza rufipogon Griff.) contains abundant drought-resistant genes, which provide an opportunity to explore these excellent resources as contributors to improve rice resistance, productivity, and quality.ResultsIn this study, we constructed four small RNA libraries, called CL and CR from PEG6000-free samples and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…It is also known to interact with MADS-box transcription factors, which is associated with stress response 79 . Besides, miR444 responded to drought stress in Dongxiang wild rice 80 . miR169d plays role in fighting drought stress in cotton 81 as well as sorghum 82 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also known to interact with MADS-box transcription factors, which is associated with stress response 79 . Besides, miR444 responded to drought stress in Dongxiang wild rice 80 . miR169d plays role in fighting drought stress in cotton 81 as well as sorghum 82 .…”
Section: Resultsmentioning
confidence: 99%
“…The growth and development processes are driven by hormonal signaling pathways that are fundamental in the response to submergence and drought in plants [ 41 ], where transcription factors and miRNAs participate. Several differentially expressed miRNAs identified in this work are known to act over target genes encoding transcription factors such as miR156 (squamosa promoter-binding protein like, SPL) [ 42 , 43 , 44 ], miR159 (giberellic acid-MYB transcription factor, GAMYB [ 28 , 29 ]), miR164 (NAM-ATAF-CUC domain transcription factor NAC, MYB [ 45 ]), miR166 (basic leucine zipper transcription factor, HD-ZIP III [ 46 , 47 ]), miR167 (auxin-responsive factor, ARF [ 30 , 35 , 48 ]), miR169 (nuclear transcription factor Y subunit alpha, NFYA [ 49 , 50 , 51 , 52 ]), miR319 (teosinte branched1/cycloidea/proliferating cell nuclear antigen factor, TCP [ 53 ]), and miR396 (growth-regulating factor, GRF [ 54 , 55 ]). Other target genes predicted in this study are listed in Table S6 .…”
Section: Discussionmentioning
confidence: 99%
“…miR171 family was identified as drought-responsive microRNAs which regulate plant response during the stress [105,106,107]. miR529 also has been shown that involved in drought stress responses [105,107,108]. The relation of miR169 and miR395 with drought responses have been previously discussed.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%